Characterization of defects in unidirectional kenaf fiber-reinforced polyurethane composites using infrared thermography technique - Dashtizadeh, Zahra (2012)
Quality control is always an important issue in industrial production. According to economics, it is more convenient to check the structural integrity and the quality of a product before it gets damaged in site. Kenaf/Polyurethane (PU) composites have potential application as “insulators” in buildings since the current insulators, such as the asbestos are dangerous for human health and can cause lung cancer. The purpose of this study was to determine the capabilities of infrared thermography in detecting and characterizing the defects in kenaf/PU composites. Kenaf/PU composites having three different weight contents (40/60, 50/50 and 60/40 Kenaf / PU weight %) were manufactured, then cut into three different thicknesses (9mm,6mm and 4mm) to study the effect of thickness on the infrared images. Active thermography method was applied and the thermal images were captured for investigating the defects. The scanning electron microscopy (SEM) was used to provide a micrograph as an evidence for the thermography results. The results show that the 6mm thickness in all cases has more defects in terms of area as compared to the 4mm and 9mm thickness. Moreover, the SEM micrographs have confirmed that the defective areas have defects such as voids, fiber pulled out, fiber break out that are the results of weak interfacial adhesion between kenaf and PU. In addition,the results also determine that voids and PU-rich zone are the defects that can be easily captured while the delamination and crack are the defects that are hard to be captured. Also, thermal images indicate that the amount of fiber plays an important role in the thermal images, since the thermal image of a 60% kenaf board is different from a thermal image of a 50% or 40% kenaf boards. Therefore, SEM morphology as evidence has proven that thermography is able to detect the surface and subsurface defects like voids and PU-rich zones.